Furious cooking : poems - Seaton, Maureen, 1947- (Iowa poetry prize., 1996)
By turns chic, romantic, sardonic, droll, seductive, and in your face, Maureen Seaton is a cornucopia of attitudes and styles, a street-smart, deeply talented woman who wryly contemplates the charades that the self and the world assume - and how hard it is to stay in focus the morning after. It gets very, very hot in Seaton's kitchen and in her poems. As this inventive and imaginative poet states, "Furious Cooking is a stew of accidents and incidents roiling across universes."